Viewing Disability in Medieval Spanish Texts : Disgraced or Graced - Scarborough, Connie L., 1954- (Book collections on Project MUSE., 2018)
This book is one of the first to examine medieval Spanish canonical works for their portrayals of disability in relationship to theological teachings, legal precepts, and medical knowledge. Connie L. Scarborough shows that physical impairments were seen differently through each lens. Theology at times taught that the disabled were "marked by God," their sins rendered on their bodies; at other times, they were viewed as important objects of Christian charity. The disabled often suffered legal restrictions, allowing them to be viewed with other distinctive groups, such as the ill or the poor. And from a medical point of view, a miraculous cure could be seen as evidence of divine intervention. This book explores all these perspectives through medieval Spain's miracle narratives, hagiographies, didactic tales, and epic poetry.